STEPPING TOGETHER "QUALITY STRATEGIES FOR UNDERSTANDING AND GUIDING HYPERACTIVE CHILDREN" - Watik, Watik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to examine the hyperactive behavior of students and their handling (case study at RA Masyithoh V) which is discussed into sub-problems, namely how is the behavior of hyperactive students at RA Masyithoh V. What efforts are made in handling students with hyperactive behavior in RA Masyithoh V. This research uses a qualitative approach, data collection techniques through observation, interviews and documentation.The results of this study indicate that the behavior of hyperactive learners is always difficult when invited to concentrate during the learning process, his attention is easily distracted especially when he feels bored. When in class he often runs here and there and often goes in and out of class for no apparent reason. They most like to disturb their friends in class. The various behaviors that students have really train the teacher's patience during the learning process.Efforts made in handling the behavior of hyperactive learners by a teacher are applying rules slowly to students, helping students in learning, using positive reinforcement. Giving the same treatment as other friends, warning his classmates not to anticipate him, placing the hyperactive learners' sitting position at the front, not giving too heavy a punishment, with the punishment given hyperactive learners will feel more responsible for what they do. Motivate to be more enthusiastic in the learning process.The results of the study are expected that teachers must be more creative in managing the learning process, so that students in RA Masyithoh V can concentrate well during the learning process